Public Space as Development Control Element in Coastal Settlements of Kampung Tua Tanjung Uma, Batam - Rangkuty, Gladies Imanda Utami; Brema, Ahmad Riansyah; Suhardi, Rafi Arbarendy; Lee, Vineeta (International Journal of Built Environment and Scientific Research, 2025)
Public space is a crucial element in urban design, especially in coastal settlements, because it acts as a main factor in controlling development and creating a balance between land development and the social needs of the community. Rapid urbanization in Batam causes environmental degradation and unplanned changes in land use, limiting public access to public spaces. This research aims to identify and analyze how public space can be used effectively as an instrument to control sustainable development in Tanjung Uma. This research uses descriptive qualitative methods to analyze the role of public space in managing city growth and maintaining socio-economic balance and environmental sustainability in Kampung Tua Tanjung Uma, Batam. The research results show that the main challenges are limited accessibility, decreased environmental quality, and minimal public space facilities. Strategies for revitalizing public spaces, increasing accessibility and optimizing spatial planning are proposed to support sustainable development and improve community welfare, by involving local communities in managing public spaces.